B— Bistochastic Quadratic Stochastic Operators and Their Properties. (March 2016) - Mukhamedov, Farrukh; Embong, Ahmad Fadillah
Abstract: In the present paper, we consider a class of quadratic stochastic operators (q.s.o.) called 6-bistochastic q.s.o. We study several descriptive properties of b - bistochastic q.s.o. It turns out that, upper triangular stochastic matrix defines a linear b -stochastic operator. This allowed us to find some sufficient conditions on cubic stochastic matrix to be a b —bistochastic q.s.o.